Acute lung injury in patients with COVID‐19 infection. Issue 1 (31st March 2020) - Li, Liyang; Huang, Qihong; Wang, Diane C.; Ingbar, David H.; Wang, Xiangdong
Abstract: During the 2020 Spring Festival in China, the outbreak of a novel coronavirus, named COVID‐19 by WHO, brought on a worldwide panic. According to the clinical data of infected patients, radiologic evidence of lung edema is common and deserves clinical attention. Lung edema is a manifestation of acute lung injury (ALI) and may progress to hypoxemia and potentially acute respiratory distress syndrome (ARDS). Patients diagnosed with ARDS have poorer prognosis and potentially higher mortality. Although no effective treatment is formally approved for COVID‐19 infection, support of ventilation with oxygen therapy and sometimes mechanical ventilation is often required. Treatment with systemic and/or local glucocorticoids might be helpful to alleviate the pulmonary inflammation and edema, which may decrease the development and/or consequences of ARDS. In this article, we focus on the lung edema and ALI of patients with this widely transmitted COVID‐19 infection in order to provide clinical indications and potential therapeutic targets for clinicians and researchers.